Somatic alterations of TP53 and MDM2 associated with response to enfortumab vedotin in patients with advanced urothelial cancer - Jindal, Tanya; Zhu, Xiaolin; Bose, Rohit; Kumar, Vipul; Maldonado, Edward; Deshmukh, Prianka; Shipp, Chase; Feng, Stephanie; Johnson, Michelle S.; Angelidakis, Austin; Kwon, Daniel; Borno, Hala T.; et al. (Frontiers in Oncology, 2023)
Background: Enfortumab vedotin (EV) is an antibody-drug conjugate approved for patients with treatment-refractory advanced urothelial carcinoma (aUC), however data on biomarkers of response is lacking. Methods: We retrospectively identified all aUC patients at our institution who received EV monotherapy and had next-generation sequencing (NGS) data available. Patients were considered responders if they had a complete response or partial response on restaging scans during treatment. Observed response rate (ORR) was evaluated by local investigator and compared between responders and non-responders using Chi-squared test. A univariable analysis was conducted using the Cox proportional hazard test to assess for associations between baseline characteristics and most common somatic alterations (in ≥10% of patients) with patient survival outcomes [progression-free survival (PFS) and overall survival (OS)]. Somatic alterations were then individually evaluated in separate multivariate models while accounting for patient and clinical characteristics using Cox regression models. Results: Among 29 patients treated with EV monotherapy, 27 had available NGS data. Median age was 70, 24 (83%) were men, 19 (62%) were Caucasian, 15 (52%) had pure urothelial histology and 22 (76%) had primary tumor in the bladder. ORR was 41%, and PFS and OS for the overall cohort were 5.1 months and 10.2 months. Responders were enriched among patients with TP53, KDM6A and MDM2 alterations. Patients with these alterations, as well as those with composite TP53/MDM2 alterations (alterations in either TP53 or MDM2), also had increased ORR with EV treatment compared to patients without these alterations. In the univariable analysis, baseline albumin level ≥ 3.0g/dL and presence of composite TP53/MDM2 alterations were associated with a prolonged OS. Baseline ECOG 0/1, TP53 alterations and TP53/MDM2 alterations were associated with a prolonged PFS. In the multivariable analysis, TP53 and TP53/MDM2 alterations were genomic markers predictive of improved PFS after accounting for the relevant clinical characteristics. Conclusion: In this single-center retrospective analysis of aUC patients treated with EV, presence of TP53 or MDM2 somatic alterations, lower ECOG PS scores (ECOG 0 or 1) and higher albumin levels (≥3 g/dL) were associated with improved outcomes with EV treatment. Prospective and external validation of these findings in larger cohorts is warranted.